Clinical Efficacy and Predictive Molecular Markers of Neoadjuvant Gemcitabine and Pemetrexed in Resectable Non-Small-Cell Lung Cancer - Bepler, Gerold (2008)
BACKGROUND: A trial of neoadjuvant gemcitabine and pemetrexed (GP) chemotherapy in patients with resectable non-small cell lung cancer was conducted. The goal was to achieve a disease response rate of 50% and to determine if the expression levels of genes associated with gemcitabine and pemetrexed metabolism are predictive of response. METHODS: Patients had staging with a computed tomography (CT) scan, whole body F-18 fluorodeoxyglucose positron emission tomography (PET), and mediastinoscopy. Four biweekly cycles of GP were given. Patients were restaged, and those with resectable stage IB-III disease had thoracotomy. Fresh frozen tumor specimens were collected before and after chemotherapy and the mRNA levels of 14 target genes determined by real-time reverse transcriptase polymerase chain reaction (RTPCR). RESULTS: Fifty-two patients started therapy. The radiographic disease response rate was 35% (95% confidence interval [CI] 21.7 to 49.6%), and the progression rate was 6%. Forty-six patients had a thoracotomy. The complete tumor resection rate was 77% (40/52). There were no perioperative deaths or deaths related to chemotherapy. Tumor response to chemotherapy was inversely correlated with the level of expression of RRM1 (p ≤ 0.001; regulatory subunit of ribonucleotide reductase) and TS (p = 0.006; thymidylate synthase); i.e., the reduction in tumor size was greater in those with low levels of expression. CONCLUSIONS: Neoadjuvant GP is well tolerated and produces an objective response rate of 35%. Tumoral RRM1 and TS mRNA levels are predictive of disease response and should be considered as parameters for treatment selection in future trials with this regimen.